PERSONAL FEATURES OF CHILDREN AND TEENAGERS OF THE UZBEK POPULATION IN SOME SOMATIC DISEASES - Arzikulov, Абдурайим (International Journal of Scientific Pediatrics, 2025)
The article is devoted to the study of personality characteristics of children and adolescents of the Uzbek population in some somatic diseases. Objects of study: An in-depth clinical and psychological examination of the contingent of children with some somatic diseases (peptic ulcer of the stomach and duodenum, acute leukemia, neurocirculatory dystonia) who were hospitalized in children's clinics of the ASMI. In individuals included in this group, neurocirculatory dystonia was verified for hyper hypotonic and cardiac type (NCD) (41 children), acute leukemia (OL) (43 children), gastric and duodenal ulcer (UB) (32 children). Objective: To identify personality characteristics in children and adolescents of the Uzbek population and their role in the development and stabilization of certain somatic diseases. Research method: Experimental, medical and psychological examination of the emotional personality sphere of children and adolescents. Results obtained: Data on personality-characterological features in children with neurocirculatory dystonia, acute leukemia and peptic ulcer of the stomach and duodenum are obtained. The revealed features of temperament and psychoemotional excitability in children and adolescents against unfavorable family and other social factors are premorbid factors in the development and manifestation of gastric and duodenal ulcer, leukemia, and neurocirculatory dystonia. Children with peptic ulcer of the stomach and duodenum, leukemia and neurocirculatory dystonia differ from healthy peers in general high accentuation.